Penyebab dan Pengelolaan Sindroma Mulut Terbakar - Titiek Setyawati (Faculty of Dentistry, Universitas Indonesia, 2015)
Burning Mouth Syndrome is a syndrome characterized by burning sensation on one or several oral structure. Clinicians usually confused by the patient complaints because of the limited experience in determining the etiology which will affect the treatment. The purpose of this study is to remind the dentist about the multifactorial etiology of Burning Mouth Syndrome that might be useful in its management. There are three etiological factors such as local, systemic and psychogenic. Management of BMS are finding out oral or systemic etiological factors and gave treatment accordingly. In persistent BMS, psychological screening and treatment should be made if necessary.